What causes the inverse relationship between primary production and export efficiency in the Southern Ocean?. Issue 9 (7th May 2016) - Le Moigne, Frédéric A. C.; Henson, Stephanie A.; Cavan, Emma; Georges, Clément; Pabortsava, Katsiaryna; Achterberg, Eric P.; Ceballos‐Romero, Elena; Zubkov, Mike; Sanders, Richard J.
Abstract: The ocean contributes to regulating atmospheric CO2 levels, partly via variability in the fraction of primary production (PP) which is exported out of the surface layer (i.e., the e ratio). Southern Ocean studies have found that contrary to global‐scale analyses, an inverse relationship exists between e ratio and PP. This relationship remains unexplained, with potential hypotheses being (i) large export of dissolved organic carbon (DOC) in high PP areas, (ii) strong surface microbial recycling in high PP regions, and/or (iii) grazing‐mediated export that varies inversely with PP. We find that the export of DOC has a limited influence in setting the negative e ratio/PP relationship. However, we observed that at sites with low PP and high e ratios, zooplankton‐mediated export is large and surface microbial abundance low suggesting that both are important drivers of the magnitude of the e ratio in the Southern Ocean. Key Points: High productivity low export regions are widespread in the Southern Ocean This may be due to high surface bacterial activity and low fecal pellet export in high PP regions These two processes must be implemented in POC export algorithms